Accepting Restrictions and Compliance With Recommended Preventive Behaviors for COVID-19: A Discussion Based on the Key Approaches and Current Research on Fear Appeals - Demirtaş-Madran, H. Andaç (Frontiers in Psychology, 2021)
COVID-19 (Coronavirus disease 2019) is a novel coronavirus which was first detected in late December 2019 in the Wuhan Province of China. This novel coronavirus, caused by a zoonotic beta-coronavirus (SARS-CoV-), is described as highly infectious. The World Health Organization (WHO) named the novel coronavirus as COVID-19 on February 11, 2020, and declared it as a “pandemic.” Almost all countries have undertaken wide-scale precautions so as to prevent or limit the spread of the virus, with most having practiced some form of “lockdown” along with “social distancing,” as well as dispensed recommendations for proper hand washing, avoiding touching the face, wearing facemasks, and using disposable tissues when either coughing or sneezing. Whereas it is well known that slowing the spread of this new epidemic requires the cooperation of all citizens, some people still seem to willfully disregard the rules and guidelines, and thereby ignore the health risks posed to both themselves and to others they come into contact with. People have responded differently to lockdown rules and social distancing practices. Whilst the majority follow the rules and recommendations with great care, others are more lax or simply refuse to comply. These differences might be accounted for according to a number of factors including personal, social, cultural, mental, and economic variables. Being persuaded to comply with preventive rules, especially those concerned with health-related behaviors, also bring certain other factors into play. Fear is one of those factors, and is one of the most powerful. It is well known that fear-based appeals can be effective in inculcating health behaviors, with many theories having been developed in this area. However, both the content of the message (the level of the fear it contains) and certain personal variables can determine the persuasive power of the fear appeal. It can even have an adverse effect if not properly applied. Many theories have been developed to address the persuasive effectiveness of the fear appeal (e.g., fear-drive theory, protection-motivation theory), and this study aims to discuss these individual differences in precautionary and preventive measures for the COVID-19 pandemic within the framework of the basic assumptions of these theoretical approaches.